2019
DOI: 10.1111/afe.12324
|View full text |Cite
|
Sign up to set email alerts
|

Conifer responses to a stylet‐feeding invasive herbivore and induction with methyl jasmonate: impact on the expression of induced defences and a native folivore

Abstract: 1 Trees attacked by multiple herbivores need to defend themselves against dynamic biotic challenges; appropriate responses to one stressor can elicit hormonal responses that are antagonistic to another. Hemlock (Tsuga canadensis) infestation by hemlock woolly adelgid (HWA; Adelges tsugae) results in the accumulation of the defensive hormone salicylic acid. 2 We explored the potential for HWA infestation to interfere with anti-folivore-induced defence signalling and its implications for a native folivore (hemlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…JA is considered to be the primary regulator of plant defence against phytophagous insects, while SA is considered to be the dominant hormone regulating defence against pathogens (Glazebrook, 2005). JA‐Me, the methyl ester of JA, is known to play important roles in transmission of plant defence signals (Huang et al, 2015; Ye et al, 2019) and regulation of insect‐induced defence responses (Rigsby et al, 2019). In this study, we found that JA‐Me levels were higher in both the interior and exterior tissues of galls sampled from the resistant EA species compared to the more susceptible DH201‐2 at the early gall developmental stage only.…”
Section: Discussionmentioning
confidence: 99%
“…JA is considered to be the primary regulator of plant defence against phytophagous insects, while SA is considered to be the dominant hormone regulating defence against pathogens (Glazebrook, 2005). JA‐Me, the methyl ester of JA, is known to play important roles in transmission of plant defence signals (Huang et al, 2015; Ye et al, 2019) and regulation of insect‐induced defence responses (Rigsby et al, 2019). In this study, we found that JA‐Me levels were higher in both the interior and exterior tissues of galls sampled from the resistant EA species compared to the more susceptible DH201‐2 at the early gall developmental stage only.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced performance of gypsy moth larvae reared on adelgid‐infested foliage may result from adelgid‐induced changes to hemlock defences. Adelgid infestation of hemlock increases foliar emissions of methyl SA (Pezet et al ., ; Pezet & Elkinton, ) and triggers SA accumulation in needles (Schaeffer et al ., ; Rigsby et al ., ), activating SA‐linked stress responses in hemlock. The accumulation of SA, and subsequent monomerisation of NPR1, has been shown to inhibit JA biosynthesis and JA‐responsive gene expression (Zarate et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in the hemlock system suggests that adelgid‐induced phytochemical changes may influence interactions between hemlock and other herbivores (Schaeffer et al ., ; Wilson et al ., ; Rigsby et al ., ). Larvae of the native hemlock looper ( Lambdina fiscellaria ) had higher survival and enhanced larval development when reared on adelgid‐infested versus uninfested hemlock foliage (Wilson et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Currently, >80% of studies on JA–SA interactions have indicated that the interaction between the JA and SA pathways is reciprocally antagonistic [ 5 ]. Most of these studies focused on gene transcript levels and protein abundances in the upstream part of these pathways, with only a few focusing on the changes in downstream metabolites, which are particularly important for the ecological outcome of plant interactions with other organisms [ 5 , 6 ]. This may be because it is difficult to accurately detect and quantify the many diverse metabolites that are produced as a result of the interaction between the JA and SA pathways [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%